Efficacy of Botanicals against Suidasia nesbitti Hughes (Acari: Suidasiidae) in Stored Pearl Millet Grains - Seema,; Gulati, Rachna; Devi, Poonam; Dalal, Gourav (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during 2020 at CCS Haryana Agricultural University, Hisar to bioassay the aqueous extract of Aonla fruits, lemon and orange peels against Suidasia nesbitti in pearl millet grains. Higher concentrations of botanicals (4 and 8%) caused 100% mortality as no mites were recorded in these treatments after 15 days as compared to significantly higher mites at 0.5 (30 mites), 1 (24.33 mites) and 2% (18 mites) concentration. Among the three botanicals, the orange peel extract was more potent than other two botanicals (anola fruit and lemon peel) as it caused 100% mortality in S. nesbitti population. No mite was recorded at all the concentrations after 1day of treatment. Lemon peel at 8% concentration caused 100% mortality in S. nesbitti within 3 h of treatment as no mite was recorded. No mite was recovered from 4% lemon peel and 4 and 8% Aonla fruit extract treated grains after 1 day of treatment. Higher concentrations of 4 and 8% of Aonla fruit provided 100% protection against S. nesbitti mite mortality. The LC50 (concentration at which 50% mortality occurred in S. nesbitti population) value was 0.64% in lemon peel extract while it was 1.38% in Aonla fruit extract against S. nesbitti. The intercept value was 4.74 and 5.24 for Aonla fruit and lemon peel extract, respectively. Bioassay results revealed acaricidal activity of aqueous extracts of three botanicals against S. nesbitti.